Analysis of Deixis in The Short Story Beauty and The Beast - Ines Alevia Sandoval; I Gusti Ngurah Parthama; Nissa Puspitaning Adni (IKIP Siliwangi, 2024)
This study conducts an analysis of deixis within selected excerpts from